Preparation method and application of CoFe2O4 / FeOOH (at) IF self-supporting electrode for efficiently electrocatalytically synthesizing ammonia

By preparing CoFe2O4/FeOOH@IF self-supporting electrode, the problem of low efficiency in the synthesis of ammonia by electrocatalytic nitrate reduction is solved, and efficient ammonia yield and Faraday efficiency are achieved, showing excellent electrocatalytic performance.

CN119776896AActive Publication Date: 2025-04-08HARBIN UNIV OF SCI & TECH

Patent Information

Application Number
CN202510116892.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-08
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

The existing electrocatalytic nitrate reduction and synthesis process is inefficient, and there is competition for hydrogen evolution reactions, making it difficult to achieve efficient ammonia yield and selectivity.

Method used

CoFe2O4/FeOOH@IF self-supporting electrode was prepared by a one-step hydrothermal method. CoFe2O4 and β-FeOOH were used to grow in situ on foam iron, and calcined in tube furnaces, CoFe2O4/FeOOH@IF self-supporting electrode was prepared to increase the contact area between the active substance and the reaction substance and the electron conduction rate.

Benefits of technology

Under alkaline conditions, efficient ammonia yield and Faraday efficiency were achieved, with ammonia yield of 15.1 mg h-1cm-2 and Faraday efficiency reached 97.67%, showing excellent electrocatalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005258041100000011
    Figure HDA0005258041100000011
  • Figure HDA0005258041100000012
    Figure HDA0005258041100000012
  • Figure HDA0005258041100000021
    Figure HDA0005258041100000021
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a CoFe2O4 / FeOOH (at) IF self-supporting electrode for efficient electrocatalytic synthesis of ammonia. The invention relates to a preparation method and application of a CoFe2O4 / FeOOH (at) IF self-supporting electrode with high ammonia yield and Faraday efficiency in the field of nano materials. The invention aims to solve the problems of low electrochemical nitrate reduction synthesis ammonia yield and low Faraday efficiency. The preparation method comprises the following steps: taking foam iron (IF), cobalt nitrate hexahydrate, ferric trichloride hexahydrate, urea and ammonium fluoride as raw materials, preparing a CoFeOOH (at) IF precursor material through a one-step hydrothermal reaction, and then successfully preparing the CoFe2O4 / FeOOH (at) IF self-supporting electrode with high ammonia yield and Faraday efficiency through tubular furnace calcination. The CoFe2O4 / FeOOH (at) IF self-supporting electrode can be directly used as a working electrode to electrocatalyze nitrate radicals to reduce and synthesize ammonia.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ammonia synthesis by nitrate reduction, and discloses a method for preparing a self-supporting electrode for efficient electrocatalytic ammonia synthesis and application thereof. Background Art

[0002] The widespread use of artificial nitrogen fertilizers coupled with the combustion of nitrogen-containing fossil fuels has led to a serious imbalance in the global nitrogen cycle. Nitrogen oxides emitted by industrial wastewater and vehicles have also caused the accumulation of nitrogen oxides in the biosphere. Among them, nitrate is considered to be one of the primary pollutants of drinking water. Among the various methods to address nitrate pollution, catalytic conversion of it into valuable chemical products, such as NH3 (a fertilizer and emerging fuel), is one of the most practical options. At present, photocatalytic nitrate reduction to synthesize ammonia has failed to achieve high ammonia yield and selectivity, and is still some distance away from large-scale industrial application. Biocatalysis has high requirements for conditions and a long cycle. In contrast, electrocatalytic nitrate reduction (NO3 – The electrocatalytic nitrate reduction ammonia synthesis process can achieve a relatively efficient ammonia synthesis process at room temperature and pressure. However, due to the eight-electron redox and slow kinetics involved, accompanied by the competition of the hydrogen evolution reaction (HER), the efficiency of the electrocatalytic nitrate reduction ammonia synthesis process still needs to be improved. Therefore, the preparation of high-performance catalysts is one of the key technologies.

[0003] Non-precious transition metals are abundant in reserves and low in price, which can meet the needs of large-scale industrial production and are ideal raw materials for electrocatalysts. At the same time, there are unoccupied d orbitals in transition metals. They can accept NO3 - The lone pair of electrons in β-FeOOH weakens the N=O double bond and reduces the energy barrier of the catalytic reaction. Spinel CoFe2O4 is a metal oxide with good electrocatalytic performance. It has good electrical conductivity and can effectively transfer electrons. In electrocatalytic reactions, the rapid transfer of electrons is the key to improving catalytic efficiency. The good conductivity of CoFe2O4 makes it have good catalytic potential in the electrocatalytic nitrate reduction reaction. At the same time, CoFe2O4 shows good stability under alkaline conditions and is not easily oxidized or decomposed, which enables it to maintain high catalytic activity and cyclic stability during long-term electrocatalysis. The iron element in β-FeOOH material has good catalytic activity and can adsorb and activate nitrate ions. Compared with many other electrocatalytic materials, β-FeOOH has higher stability, especially under alkaline conditions, and can maintain high catalytic activity in long-term catalytic reactions.

[0004] The present invention prepares a CoFeOOH@IF precursor loaded on foamed iron (abbreviated as IF) by a one-step hydrothermal method, and further generates a CoFe2O4 / FeOOH@IF self-supporting electrode material by calcining in a tubular furnace. The method tightly combines CoFe2O4 and β-FeOOH, and grows in situ on foamed iron with a larger specific surface area and excellent conductivity. Through the synergistic effect of CoFe2O4, β-FeOOH and IF, the CoFe2O4 / FeOOH@IF self-supporting electrode exhibits excellent performance in electrocatalytic nitrate reduction, providing an important way to prepare a highly efficient electrocatalytic nitrate reduction catalyst for ammonia synthesis. Summary of the invention

[0005] The purpose of the present invention is to obtain a highly efficient electrocatalytic ammonia synthesis CoFe2O4 / FeOOH@IF self-supporting electrode, solve the problems of low yield and Faraday efficiency of electrochemical nitrate reduction ammonia synthesis, and provide a CoFe2O4 / FeOOH@IF material preparation method and application.

[0006] A method for preparing a highly efficient electrocatalytic ammonia synthesis CoFe2O4 / FeOOH@IF self-supporting electrode comprises the following steps:

[0007] 1. Dissolve cobalt nitrate hexahydrate, ferric chloride hexahydrate, urea and ammonium fluoride in distilled water at the same time, then stir for a while until the solution becomes transparent to obtain a pink solution.

[0008] The molar ratio of cobalt nitrate to ferric chloride described in step 1 is 2:(1.0-2.0);

[0009] The molar ratio of cobalt nitrate to ammonium fluoride described in step 1 is 1:(15.0-20.0);

[0010] The molar ratio of cobalt nitrate to urea described in step 1 is 1:(3.0-5.0);

[0011] The volume ratio of the amount of cobalt nitrate described in step 1 to distilled water is 1.0 mmol: (20-30) mL.

[0012] 2. Cut the foam iron into 2×3cm size and wash with acetone, 1mol·L -1 Rinse with sulfuric acid and deionized water for 5-10 minutes each.

[0013] 3. Add the pink reaction liquid to the polytetrafluoroethylene reactor, then add the cleaned foam iron, react in the polytetrafluoroethylene reactor at a temperature of 120°C for 6 hours, and then cool the polytetrafluoroethylene reactor naturally to room temperature. Take out the foam iron and wash it with distilled water and anhydrous ethanol several times. Finally, place the obtained brown foam iron in a 60°C vacuum drying oven and dry it overnight. Place the dried foam iron in a tubular furnace and heat it at 350°C for 2 hours under N2 atmosphere. The obtained black foam iron is the CoFe2O4 / FeOOH@IF self-supporting electrode;

[0014] The CoFe2O4 / FeOOH@IF self-supporting electrode was used as an electrocatalyst for the electrocatalytic reduction of nitrate to ammonia.

[0015] Compared with the prior art, this embodiment has the following characteristics:

[0016] 1. The present invention adopts a simple hydrothermal synthesis technology, using hexahydrated ferric nitrate, hexahydrated ferric chloride, urea and ammonium fluoride to dissolve in distilled water, and obtains the precursor of the CoFeOOH@IF self-supporting electrode uniformly loaded on the foamed iron through a one-step hydrothermal method. Then, the CoFe2O4 / FeOOH@IF self-supporting electrode is successfully prepared by calcining in a tubular furnace. In the preparation process, it only takes a short time to obtain a self-assembled nanomaterial with excellent performance, and no complex equipment is required.

[0017] 2. The CoFe2O4 / FeOOH@IF material prepared by the present invention is a self-supporting electrode grown in situ. The in situ growth strategy changes the disadvantage that the traditional powder catalyst needs to be coated with a binder, which can maintain the original microscopic morphology of the catalyst, increase the contact area between the active substance and the reactant, and increase the electron conduction rate, thereby promoting the electrocatalytic nitrate reduction. At pH = 13, 0.1 mol·L –1 In KOH and KNO3 electrolytes, the ammonia yield is 15.1 mg h -1 cm -2 , the Faraday efficiency reaches 97.67%. Therefore, CoFe2O4 / FeOOH@IF material has very good application value in the field of electrocatalytic nitrate reduction.

[0018] The present invention can obtain a CoFe2O4 / FeOOH@IF self-supporting electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a schematic diagram of a scanning electron microscope of the CoFe2O4 / FeOOH@IF self-supporting electrode prepared in Example 1;

[0020] Figure 2 This is a schematic diagram of a scanning electron microscope of the CoFe2O4 / FeOOH@IF self-supporting electrode prepared in Example 1;

[0021] Figure 3 Schematic diagram of powder X-ray diffraction of the CoFe2O4 / FeOOH@IF self-supporting electrode prepared in Example 1;

[0022] Figure 4 The CoFe2O4 / FeOOH@IF self-supporting electrode prepared in Example 1 was prepared at 0.1 mol·L –1 KNO3 and KOH solution and 0.1 mol·L –1 Linear sweep voltammetry test curve in KOH solution;

[0023] Figure 5 The CoFe2O4 / FeOOH@IF self-supporting electrode prepared in Example 1 was heated to 0.1 mol·L –1 Electrocatalytic synthesis of ammonia was carried out in KNO3 and KOH solution, and the UV-visible absorption spectra of ammonia were detected at different voltages;

[0024] Figure 6 Ammonia yield and Faraday efficiency of the CoFe2O4 / FeOOH@IF self-supporting electrode prepared in Example 1 at different voltages. DETAILED DESCRIPTION

[0025] The technical solution of the present invention is not limited to the specific implementation modes listed below. The specific implementation modes listed below are only used to illustrate the present invention and are not limited to the technical solution described in the embodiments of the present invention. It should be understood by those skilled in the art that the present invention can still be modified or replaced by equivalents to achieve the same technical effects. As long as the use requirements are met, they are within the protection scope of the present invention.

[0026] Specific implementation method 1: A method for preparing a CoFe2O4 / FeOOH@IF self-supporting electrode comprises the following steps:

[0027] 1. Dissolve cobalt nitrate hexahydrate, ferric chloride hexahydrate, urea and ammonium fluoride in distilled water at room temperature, and then stir for a period of time until the solution becomes transparent to obtain a pink solution.

[0028] The molar ratio of cobalt nitrate to ferric chloride described in step 1 is 2:(1.0-2.0);

[0029] The molar ratio of cobalt nitrate to ammonium fluoride described in step 1 is 1:(15.0-20.0);

[0030] The molar ratio of cobalt nitrate to urea described in step 1 is 1:(3.0-5.0);

[0031] The volume ratio of the amount of cobalt nitrate described in step 1 to distilled water is 1.0 mmol: (20-30) mL.

[0032] 2. Cut the foam iron into 2×3cm size and wash with acetone, 1mol·L -1 Rinse with sulfuric acid and deionized water for 5-10 minutes each.

[0033] 3. Add the pink reaction liquid into a polytetrafluoroethylene reactor, and then add the cleaned foam iron, react in a polytetrafluoroethylene reactor at a temperature of 120°C for 6 hours, then cool the polytetrafluoroethylene reactor naturally to room temperature, take out the foam iron, and wash it with distilled water and anhydrous ethanol for several times, and finally place the obtained brown foam iron in a 60°C vacuum drying oven to dry overnight, place the dried foam iron in a tubular furnace, and heat it at 350°C for 2 hours under a N2 atmosphere. The obtained black foam iron is the CoFe2O4 / FeOOH@IF self-supporting electrode.

[0034] Compared with the prior art, this embodiment has the following characteristics:

[0035] 1. The present invention adopts a simple hydrothermal synthesis technology, using hexahydrated cobalt nitrate, hexahydrated ferric chloride, urea and ammonium fluoride dissolved in distilled water to successfully prepare the CoFe2O4 / FeOOH@IF self-supporting electrode. This is a one-step hydrothermal method to obtain a two-component self-supporting electrode precursor of FeOOH and CoFe2O4 uniformly loaded on foamed iron. Further calcination in a tubular furnace can successfully prepare the CoFe2O4 / FeOOH@IF self-supporting electrode. In the preparation process, it only takes a short time to obtain a self-assembled nanomaterial with excellent performance, and no complex equipment is required.

[0036] 2. The CoFe2O4 / FeOOH@IF material prepared by the present invention is a self-supporting electrode grown in situ. The in situ growth strategy changes the disadvantage that the traditional powder catalyst needs to be coated with a binder, which can maintain the original microscopic morphology of the catalyst, increase the contact area between the active substance and the reactant, and increase the electron conduction rate, thereby promoting the electrocatalytic nitrate reduction. At pH = 13, 0.1 mol·L –1 In KOH and KNO3 electrolytes, the ammonia yield is 15.1 mg h -1 cm -2 , the Faraday efficiency reaches 97.67%. Therefore, CoFe2O4 / FeOOH@IF material has very good application value in the field of electrocatalytic nitrate reduction.

[0037] The present invention can obtain a CoFe2O4 / FeOOH@IF self-supporting electrode.

[0038] Specific embodiment 2: The difference between this embodiment and specific embodiment 1 is that the molar ratio of cobalt nitrate to ferric chloride is 2: 1. The other steps are the same as those of specific embodiment 1.

[0039] Specific embodiment 3: The difference between this embodiment and specific embodiments 1 to 2 is that the molar ratio of cobalt nitrate to ammonium fluoride is 1:20. The other steps are the same as those of specific embodiments 1 or 2.

[0040] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the molar ratio of cobalt nitrate to urea is 1:5. The other steps are the same as those of specific embodiments 1, 2 or 3.

[0041] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the volume ratio of the amount of cobalt nitrate to distilled water is 1 mmol:20 mL. The other steps are the same as those of specific embodiments 1 to 4.

[0042] Specific implementation method six: In this implementation method, the obtained black foam iron, namely the CoFe2O4 / FeOOH@IF self-supporting electrode, is directly used as a working electrode to electrocatalyze the reduction of nitrate to ammonia.

[0043] At pH = 13, 0.1 mol·L –1 The ammonia yield in KOH and KNO3 solution is 15.1 mg h -1 cm -2 , Faraday efficiency reaches 97.67%.

[0044] The following examples are used to verify the beneficial effects of the present invention:

[0045] Example 1: The preparation method of CoFe2O4 / FeOOH@IF self-supporting electrode is completed according to the following steps:

[0046] 1. Dissolve cobalt nitrate hexahydrate, ferric chloride hexahydrate, 6.25mmol urea and 25mmol ammonium fluoride in 25mL distilled water at the same time, and then stir the solution at room temperature for a period of time until the solution is transparent.

[0047] 2. Cut the foam iron into 2×3cm size and wash with acetone, 1mol·L –1 Clean with sulfuric acid and deionized water for 5-10 minutes each.

[0048] 3. Add the pink reaction liquid into a polytetrafluoroethylene reactor, and then add the cleaned foam iron, react in a polytetrafluoroethylene reactor at a temperature of 120°C for 6 hours, then cool the polytetrafluoroethylene reactor naturally to room temperature, take out the foam iron, and wash it with distilled water and anhydrous ethanol for several times, and finally place the obtained brown foam iron in a 60°C vacuum drying oven to dry overnight, place the dried foam iron in a tubular furnace, and heat it at 350°C for 2 hours under a N2 atmosphere. The obtained black foam iron is the CoFe2O4 / FeOOH@IF self-supporting electrode.

[0049] The CoFe2O4 / FeOOH@IF self-supporting electrode prepared in Example 1 was subjected to a scanning electron microscope (SEM) test to obtain a scanning electron microscope image of the CoFe2O4 / FeOOH@IF self-supporting electrode prepared in Example 1.

[0050] Figure 1 This is a schematic diagram of a scanning electron microscope of the CoFe2O4 / FeOOH@IF self-supporting electrode prepared in Example 1.

[0051] Depend on Figure 1 It can be seen that the CoFe2O4 / FeOOH composite material prepared in Example 1 is evenly and densely distributed on the foamed iron.

[0052] Figure 2 This is a schematic diagram of a scanning electron microscope of the CoFe2O4 / FeOOH@IF self-supporting electrode prepared in Example 1.

[0053] Depend on Figure 2 It can be seen that the CoFe2O4 / FeOOH@IF material prepared in Example 1 has a polyhedral morphology and uniformly distributed pores.

[0054] The CoFe2O4 / FeOOH@IF self-supporting electrode prepared in Example 1 was subjected to an X-ray powder diffraction (PXRD) test to obtain an X-ray powder diffraction pattern of the CoFe2O4 / FeOOH@IF self-supporting electrode prepared in Example 1, as shown in FIG. Figure 3 shown.

[0055] Figure 3 Schematic diagram of powder X-ray diffraction of the CoFe2O4 / FeOOH@IF self-supporting electrode sheet prepared in Example 1;

[0056] Figure 31 is the diffraction peak of the standard card of CoFe2O4, and the corresponding standard card number is 22-1068. The diffraction peaks 2θ=18.29°, 30.08°, 35.44°, 37.06°, 43.06°, 53.45°, 56.97°, 62.59°, 65.75°, 74.00°, 78.97°, 81.93° and 86.77° point to the (111), (220), (311), (222), (400), (422), (511), (440), (531), (533), (444), (551) and (642) crystal planes of the CoFe2O4 phase. 2 is the diffraction peak of the standard card of FeOOH, and the corresponding standard card number is 34–1266. The diffraction peaks 2θ=26.73°, 34.00°, 35.16°, 39.22°, 52.05° and 55.09° point to the (310), (400), (211), (301), (600) and (620) crystal planes of the FeOOH phase. 3 is the actual diffraction peak of the CoFe2O4 / FeOOH@IF self-supporting electrode, which is consistent with the peak position of the standard card of CoFe2O4 and FeOOH. It can be determined that the material obtained in the experiment is the CoFe2O4 / FeOOH@IF self-supporting electrode composed of CoFe2O4, FeOOH and IF, and the purity of the material is high.

[0057] The CoFe2O4 / FeOOH@IF self-supporting electrode prepared in Example 1 was subjected to a linear sweep voltammetry test, and a linear sweep voltammetry test curve of the CoFe2O4 / FeOOH@IF self-supporting electrode prepared in Example 1 was obtained. Figure 4 As shown;

[0058] from Figure 4 It can be seen that the CoFe2O4 / FeOOH@IF self-supporting electrodes prepared in Example 1 are -1 KNO3 and KOH solution, 0.1 mol·L -1 The linear sweep voltammetry test curve of KOH solution shows that within the same voltage range, the reduction current density of CoFe2O4 / FeOOH@IF in nitrate-containing electrolyte is significantly higher than that in electrolyte without nitrate, indicating that the CoFe2O4 / FeOOH@IF catalyst has good ability to electrocatalyze nitrate reduction to synthesize ammonia.

[0059] Figure 5 The CoFe2O4 / FeOOH@IF self-supporting electrode is shown in 0.1 mol·L -1 The UV-visible absorption spectra of KNO3 and KOH solutions in the synthesis of ammonia at different voltages are shown in Figure 2. Figure 5As shown, as the voltage increases, the absorbance of the electrolyte that is color-developed after the catalytic test also gradually increases with the voltage in the absorbance test.

[0060] Figure 6 The CoFe2O4 / FeOOH@IF self-supporting electrode is shown in 0.1 mol·L -1 Ammonia production and Faraday efficiency at different voltages in KNO3 and KOH solutions. Figure 6 As shown in Figure 2, at a potential of -0.74 V vs. RHE, the best Faradaic efficiency was 97.67%, corresponding to an ammonia production of 15.1 mg h –1 cm –2 , showing excellent performance in electrocatalytic nitrate reduction. Therefore, the CoFe2O4 / FeOOH@IF self-supporting electrode can be used as an efficient electrocatalytic nitrate reduction catalyst for ammonia synthesis.

[0061] In summary: the CoFe2O4 / FeOOH@IF electrocatalytic self-supporting material prepared in Example 1 has a strong ability to reduce nitrate under alkaline conditions as a catalyst, is an electrocatalyst with excellent performance, and has very good application potential for catalyzing the reduction of nitrate to synthesize ammonia.

Claims

1. A method for preparing a highly efficient electrocatalytic ammonia synthesis CoFe2O4 / FeOOH@IF self-supporting electrode and its application, comprising the following steps:

1. Dissolve cobalt nitrate hexahydrate, ferric chloride hexahydrate, urea and ammonium fluoride in distilled water at room temperature, and then stir for a period of time until the solution becomes transparent to obtain a pink solution. The molar ratio of cobalt nitrate to ferric chloride described in step 1 is 2:(1.0-2.0); The molar ratio of cobalt nitrate to ammonium fluoride described in step 1 is 1:(15.0-20.0); The molar ratio of cobalt nitrate to urea described in step 1 is 1:(3.0-5.0); The volume ratio of the amount of cobalt nitrate described in step 1 to distilled water is 1.0 mmol: (20-30) mL.

2. Cut the foamed iron (IF) into 2×3 cm size and successively use acetone, 1 mol·L -1 Clean with sulfuric acid and deionized water for 5-10 minutes each.

3. Add the pink reaction liquid to the polytetrafluoroethylene reactor, then add the cleaned foam iron, react in the polytetrafluoroethylene reactor at 120°C for 6 hours, then cool the polytetrafluoroethylene reactor naturally to room temperature, take out the foam iron, wash it with distilled water and anhydrous ethanol for several times, and finally dry the obtained brown foam iron in a 60°C vacuum drying oven overnight. Place the dried foam iron in a tubular furnace and heat it at 350°C for 2 hours under N2 atmosphere, and the obtained black foam iron is the CoFe2O4 / FeOOH@IF self-supporting electrode.

2. The method for preparing a highly efficient electrocatalytic ammonia synthesis CoFe2O4 / FeOOH@IF self-supporting electrode according to claim 1, characterized in that The molar ratio of cobalt nitrate to ferric chloride described in step 1 is 2:

1.

3. The method for preparing a highly efficient electrocatalytic ammonia synthesis CoFe2O4 / FeOOH@IF self-supporting electrode according to claim 1, characterized in that The molar ratio of cobalt nitrate to ammonium fluoride in step 1 is 1:

20.

4. The method for preparing a highly efficient electrocatalytic ammonia synthesis CoFe2O4 / FeOOH@IF self-supporting electrode according to claim 1, characterized in that The molar ratio of cobalt nitrate to urea in step 1 is 1:

5.

5. The method for preparing a highly efficient electrocatalytic ammonia synthesis CoFe2O4 / FeOOH@IF self-supporting electrode according to claim 1, characterized in that The volume ratio of the amount of cobalt nitrate described in step 1 to distilled water is 1mmol:20mL.

6. The use of the CoFe2O4 / FeOOH@IF self-supporting electrode according to claim 1, characterized in that the catalyst CoFe2O4 / FeOOH@IF is directly used as a working electrode to electrocatalyze the reduction of nitrate to ammonia.

Citation Information

Patent Citations

  • Preparation method and application of cobalt-iron composite oxide nanorods for lithium ion battery anode material

    CN104852042A

  • Preparation method and application of Co-doped FeOOH catalyst

    CN119101942A

Cited By

  • Composite material for electro-catalytic nitrate reduction and preparation method and application thereof

    CN121107535A